Combining biologic and phototherapy treatments for psoriasis: safety, efficacy, and patient acceptability - Farahnik B; Patel V; Beroukhim K; Zhu TH; Abrouk M; Nakamura M; Singh R; Lee K; Bhutani T; Koo J (Dove Medical Press, 2016)
Benjamin Farahnik,1 Viraat Patel,2 Kourosh Beroukhim,3 Tian Hao Zhu,4 Michael Abrouk,2 Mio Nakamura,5 Rasnik Singh,3 Kristina Lee,5 Tina Bhutani,5 John Koo5 1University of Vermont College of Medicine, Burlington, VT; 2School of Medicine, University of California, Irvine, 3David Geffen School of Medicine, University of California, Los Angeles, 4University of Southern California Keck School of Medicine, Los Angeles, 5Department of Dermatology, Psoriasis and Skin Treatment Center, University of California, San Francisco, CA, USA Background: The efficacy and safety of biologic and phototherapy in treating moderate-to-severe psoriasis is well known. However, some patients may not respond well to biologic agents or phototherapy on their own and may require combination therapy. Skillfully combining a biologic agent and phototherapy may provide an additive improvement without much increase in risks.Objective: To summarize the current state of evidence for the efficacy and safety of combining biologics with phototherapy in the treatment of moderate-to-severe plaque psoriasis.Methods: We conducted an extensive search on Pubmed database for English language literature that evaluated the use of a combination of biologic and phototherapy for the treatment of moderate-to-severe psoriasis through January 2016. The search included the following keywords: psoriasis, etanercept, adalimumab, infliximab, ustekinumab, biologics, phototherapy, and combination therapy.Results: The primary literature included randomized controlled trials, a head-to-head study, open-label controlled and uncontrolled trials, case series, and case reports. Etanercept was used in over half of the reported cases, but other biologic agents used included ustekinumab, adalimumab, and infliximab. The vast majority of phototherapy was narrowband ultraviolet B (NBUVB) radiation. Most cases reported enhanced improvement with combination therapy. Serious adverse events throughout the study duration were reported in <3% of the patients. Long-term adverse events cannot be excluded.Conclusion: Combination of biologic and phototherapy appears to be a viable clinical strategy in the treatment of moderate-to-severe psoriasis not responsive to monotherapy, despite limitations in the data available. NBUVB in combination with biologics appears to be especially effective. However, the long-term impact of these combinations is yet to be determined. Keywords: psoriasis, biologics, phototherapy, UVB, UVA, combination therapy